The Clinical and Sonographic Features of Cervical Muscle Involvement in Patients with Frozen Shoulder: A Retrospective Study - Alice Chu-Wen Tang; Shih-Ting Huang; Szu-Yuan Wu; Simon Fuk-Tan Tang (Biomedicines, 2024)
Background/Objectives: Frozen shoulder is a common shoulder disorder that often places limitations on the range of motion of the shoulder. The disease may induce neck pain due to overuse of the neck muscle in an attempt to compensate for lack of shoulder movement. In clinical practice, swelling and inflammation of the scalene and levator scapulae may be detected via sonography in patients with frozen shoulder. The aim of this study was, therefore, to determine whether the involvement of the scalene complex or levator scapulae could compensate for the limited motion of the shoulder in patients with frozen shoulder. Methods: We retrospectively reviewed the medical records of 362 patients with unilateral frozen shoulder. These patients were divided into four groups depending on the involvement of the scalene complex or levator scapulae muscle. The range of motion of the shoulder—encompassing flexion, abduction, and external rotation—was measured with a goniometer. We also performed an ultrasound scan on each shoulder. The involvement of the scalene complex and levator scapulae muscle was also assessed via musculoskeletal ultrasound. Results: The range of motion of the shoulder in terms of flexion, abduction, external rotation, and total range of motion differed significantly between the four groups (p < 0.05). Patients in whom the scalene complex or levator scapulae muscle was involved demonstrated a significantly wider range of motion in different shoulder directions than patients without the involvement of those muscles (p < 0.05). Conclusions: A greater range of motion in the shoulder can be obtained through the activation of the scalene complex or levator scapulae muscle, which act to compensate for the lack of shoulder movement in patients with frozen shoulder. These two muscles showed thickening and hypoechoic changes upon sonography.